(3fMh JfXje bGfhfi NGU doebpqOe (B((3oeQpqMd(B) (3GdHVGFY ai YedjGJ Gdfbd GdHMQi (B/ s - (3BSQ eMeO CHhVja Cejfs; (3SejMI eUWai GdbdjhHi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3deG cGf oeQMd GdHVGFY TNUG ef CTNGU GdedGMI GdHMQjI h GdPi de ojhnVY dg JfXje ai GdJTQjY GdeUQi(B: (3h de jcf dg OQGSI eSJbdI h eJcGedI(B: (3aEf Pdc cGf OGaYkG dJfGhdg cHMK eSJbd h eJcGed; dEjVGM eaghe oeQMd GdHVGFY h EHQGR eQGcRg GdbGfhfjI(B: (3h cPdc JhVjM Mbhbg h GdJRGeGJg h eSFhdjJg GdbGfhfjI ai cd hXjaI ef hXGFag JHYG deQcRg GdbGfhfi(B: (3MjK Efg HOC chcjd Yf CUMGH GdHVGFY (B- (3hcjd HCLQ(B- (3Ke JWhQ Edi Cf UGQ hcjdG HGdYehdI ddfbd(B: (3Ke RGO JWhQg Edi Cf CUHM fGbdkG CUjdkG coeJYgO ddfbd oeJYOO GdhSGFW h oeJYgO dddhLSJjGJ(B. (3CjVG Je GdSYi dHjGf fTCI GdoeQMd h JWhQg h GdefXeGJ GdbGFeI Ydi eUGdMg(B: (3h HjGf YbO GdJQMjd HUaI YGeI h GdfXe GdbGfhfjI GdJi ojHnQe ajgG GdYbO h eYGjjQ GdJaQbI Hjf chfg hcjdG ChCUjdG(B: (3h HjGf eGgjI eaGhVGJ YbO GdJQMjd (B:(3oeSJYjfkG HGdefgL GdhUai GdJMdjdi ;dGSJbUGA GdHMKs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2015s
(3HHdjhLQGajG(B: (3UaMGJ (B316-329s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3eQMd GdHVGFYs; (3fbd GdHVGFYs; (3YbO JQMjd GdHVGFYs; (3hcjd GdYHhQs; (3Gdhcjd HGdYehdIs; (3GJaGbjI GdGee GdeJMOI ddfbd GdOhdis; (3ZQaI GdJLGQI GdOhdjIs; (3GdjhfcJGOs; (3bhGYO GdajGJG GdGfehPLjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs